Ligações em silos metálicos de chapas corrugadas: proposta de um parafuso alternativo - Ficanha, Daniele Cristina (2016)
The function of metal silos consists in storing and preserving the quality of the grains. For that, it is extremely important the correct dimensioning in order to guarantee efficiency and security of the set. The possibility of a metal silo implantation is based mainly in the cost and weight of the primary raw material, the steel. The side plates represent the biggest part of the raw material used. The feasibility of a new fixation element, the alternative bolt, responsible for the connections of the silo body’s elements increase the resistance of the side plate, becoming attractive and economic for all users of metal silos. The elaboration of an alternative bolt was based on ISO 4016 (2000) regarding chemical composition and mechanical properties. Mass from the hexagonal head of the traditional bolt was withdrawn and added in the cut plan of the alternative bolt, making it an oblong element and round head. Prototypes of the alternative bolt were developed with the same raw material, temper process and bichromatization as the executed in the traditional bolts. Twenty-three samples of the traditional bolt and sixteen samples of the alternative bolt were produced through the method of direct shearing. The model’s premises were verified, in which the increase in shearing area in the alternative bolt’s cutting plan produced effects in the shearing resistance in the traditional bolt. Through the result of the alternative bolt, it was possible to determine the random error average variable of the model , validating the theoretical functions of the probability distribution for the representation of the statistic information of this random variable, determining the correct strength of the alternative bolt as 107,40 kN. In order to use the alternative bolt in metal silos, 27 samples of the traditional bolt and 3 samples of the alternative bolt were compared, both using support plates of the same material used in the silos, to verify if the plate influences the bolt’s shearing resistance. The parameters used in the definition of the crushing and tearing resistance were determined by tensile tests on the support plates, quantification to the breaking point, as well as the distance between the hole and the edge were determined, to be superior to the resistance of the bolts calculations. It was not possible to determine the influence of the support plate in the resistance of the alternative bolt shear, since the support plate crushed it and it reached only deformed plastic state. The comparison between the averages for the sample of the alternative bolt may have produced positive effects in the shear bolt resistance.